Evaluation of MR-angiography for pre-operative assessment of living kidney donors - Proßt, Rüdiger Lothar; Domínguez Fernández, Emilio; Neff, Wolfgang; Braun, Claude; Neufang, Thomas; Post, Stefan (Clinical transplantation, 2005)
Abstract: Introduction: Pre-operative magnetic resonance tomography (MR) and MR-angiography (MRA) have rendered favorable results for the assessment of renal anatomy preceding living-related kidney transplantation. However, limited value of MRA in the detection of accessory renal vasculature is reported. Methods: We compared the results of pre-operative contrast-medium-enhanced MRA of the last 30 consecutively performed nephrectomies in living kidney donors with the intraoperative findings of vascular, parenchymal, and ureteral anatomy. Results: Pre-operative MRA diagnosed a solitary renal artery in 24 cases (80%) and a normal venous, ureteral and parenchymal anatomy in all cases. Intraoperatively, the surgeon confirmed the normal pre-operative MRA findings of ureter and parenchyma. Yet, in 6 out of 30 patients (20%) vascular architecture differed from the pre-operative imaging: four of them, who had a radiologically regular anatomy, were found to have accessory vessels upon surgical preparation. In the fifth patient, MRA revealed an accessory lower polar artery, which was confirmed during surgery. An undiagnosed third arterial vessel, located behind the renal vein, led to an aortic bleeding. In the sixth case, the adrenal gland artery was misinterpreted as an accessory superior polar artery of the kidney in MRA. Additionally, a radiologically undetected inferior polar artery was dissected during nephrectomy and led to partial hypoperfusion of the graft. Subsequent retrospective reevaluation of the MRA by experienced radiologists was unable to identify the intraoperative anatomical discrepancies. Hence, sensitivity of MRA was 60% (6 out of 10 cases) for accessory renal vessel detection and 80% (24 out of 30 cases) for overall sensitivity in determining renal vessel number. Discussion: MRA is a reliable method for the non-invasive investigation of living kidney donors and provides valuable information required by the surgeon. But, as the technique misses small diameter vessels, it cannot be recommended as sole diagnostic tool in unclear cases.
Gesehen am 31.05.2022